2002
DOI: 10.1046/j.1463-1318.2002.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proliferation of a colon cancer cell line by indole‐3‐carbinol

Abstract: OBJECTIVE: To observe the effect of Indole-3-carbinol (I3C), a naturally occurring component of cruciferous vegetables, on cell proliferation of a colon cancer cell line. METHODS: Cell proliferation was measured using three different methods; 3H-thymidine incorporation, cell count and colourimetric assay. RESULTS: Each method of measurement revealed that I3C significantly reduced cell proliferation at concentrations of > 0.1 mM. CONCLUSION: The present study demonstrates for the first time the capacity of indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 7 publications
3
28
0
Order By: Relevance
“…I3C has been shown to suppress the proliferation of a wide variety of cells, including breast cancer cells, [9][10][11][12] colon cancer cells, [13][14][15] prostate cancer cells, 16,17 and endometrial cancer cells. 18 Katdare's group showed that I3C inhibits benzopyrene-induced proliferation of mammary epithelial cells.…”
Section: Antiproliferative Effects Of I3c Against Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…I3C has been shown to suppress the proliferation of a wide variety of cells, including breast cancer cells, [9][10][11][12] colon cancer cells, [13][14][15] prostate cancer cells, 16,17 and endometrial cancer cells. 18 Katdare's group showed that I3C inhibits benzopyrene-induced proliferation of mammary epithelial cells.…”
Section: Antiproliferative Effects Of I3c Against Tumor Cellsmentioning
confidence: 99%
“…Using an in vitro system and a hepatic postmitochondrial fraction from mice that had been treated by gavage with I3C, they found that up to 90% of the covalent binding of BaP metabolites to macromolecules was eliminated, while AHH activity was unchanged. In experiments in vivo, treatment of mice by gavage with I3C before [ 14 C]BaP resulted in up to an 80% decrease in covalent binding of 14 C to DNA or protein with no concomitant decrease in hepatic AHH activity. These results suggest that I3C administered in vivo confers protection against the binding of BaP oxidation products to hepatic cellular macromolecules.…”
Section: I3c Prevents Carcinogen-dna Adduct Formationmentioning
confidence: 99%
“…The antiproliferative activity of some substituted indole and biindole derivatives against breast, colon, and lung cancer cells has been reported (Katdare et al, 1998;Chinni and Sarkar, 2002;Frydoonfar et al, 2002Frydoonfar et al, , 2003Hong et al, 2002;Howells et al, 2002;Zheng et al, 2002;Hudson et al, 2003;Nachshon-Kedmi et al, 2003;Rahman et al, 2003;Weng et al, 2008;Ji et al, 2013;Ali et al, 2014). The antiproliferative and cytotoxic activities of 2 against HeLa, C6, and HT29 cell lines were tested and documented for the first time in this study.…”
Section: Discussionmentioning
confidence: 67%
“…[91] Indole-3-carbinol (I3C) and its derivatives ( Figure 20) are a class of compounds that have received considerable attention over the past 30 years. [92,93] I3C has been shown to be effective against a range of cancers including those of the breast, [94] colon [95][96][97] and prostate. [98][99][100] The activity of I3C is belived to be due to its intrinsic instability in acidic media, and the subsequent formation of its metabolites (Figure 20).…”
Section: Ros Producersmentioning
confidence: 99%